A new paradigm for accident investigation and analysis in the era of big data. Issue 1 (18th May 2017) - Huang, Lang; Wu, Chao; Wang, Bing; Ouyang, Qiumei
Abstract : The advent of the era of Big Data has spawned a new research paradigm and has transformed the outlook of numerous fields in science and engineering. Similarly, as one of the important fields of safety science, the area of accident investigation also has great opportunities for leveraging Big Data to its advantage. With this in mind, in this article, the influencing factors of accident investigation were analyzed. Then, the definition of Safety‐related Big Data (SRBD) was analyzed, and a four‐layer pyramidal structure consisting of SRBD, Safety Information, Safety Law, and Safety Knowledge was constructed. Based on this, the conceptual model of the accident investigation paradigm based on SRBD was proposed. Moreover, the opportunities offered by the proposed new paradigm were argued from three aspects, which are "tools, " "inputs, " and "constraints." Last, the proposed paradigm was applied in a case study. Results show that the proposed paradigm can provide a novel method for accident investigation and analysis. The presented paper aims to explore the great expectations for accident investigation in the era of Big Data. © 2017 American Institute of Chemical Engineers Process Process Saf Prog 37:42–48, 2018